Sustainable production systems of urban agriculture in the future: a case study on the investigation and development countermeasures of the plant factory and vertical farm in China - Wang, Xinfa; Onychko, Viktor; Zubko, Vladislav; Wu, Zhenwei; Zhao, Mingfu (Frontiers in Sustainable Food Systems, 2023)
The plant factory and vertical farm are new sustainable agricultural production systems developed rapidly in the world in recent years. At present, the academic and industrial circles in China have a high degree of participation and enthusiasm in the development of plant factories and vertical farms. However, due to the issues of high initial construction and later operation costs, low comprehensive utilization of resources, less product diversity, low market share, high price and low core competitiveness, the government, production enterprises, sales companies and consumers have low recognition and satisfaction, and different attitudes. The government's policy support is not high, the production capacity of production enterprises is low, the enthusiasm of sales companies is not high, the promotion and publicity is not strong, and consumers are not satisfied, which are the key factors restricting its sustainable development. Based on these obstacles, questionnaire questions and options were designed from the perspective of industrialization, commercialization and sustainable development, in order to understand the respondents' cognitive level, doubts and concerns, purchase intention and consumption expectation of this new agricultural production system and its products, as well as their trust and recognition of brand products. This paper analyzes the group structure of the participants from the management, R & D, production, sales, consumption, regional development and other industrial fields to determine the scope of the respondents. Electronic questionnaires and face-to-face interviews were used in the survey. The questionnaire is in the form of an online questionnaire, which is pushed to social groups through social media platforms. A total of 729 valid questionnaires have been received. This research project uses descriptive statistics, multi-factor cross-analysis and other statistical methods to classify, summarize, statistics and analyze the questionnaire. From the point of view of social relations, the social roles, functions and interaction modes of different practitioners in the plant factory industry, as well as the survey results were studied and analyzed, and the corresponding development ideas and suggestions were put forward. It can provide researchers, producers, sellers and managers with comprehensive information such as social demand, market status and future development direction for development planning and decision-making reference.